Adaptive damping tuning and circuit implementation for broad bandwidth energy harvesting. (20th October 2020) - Sharma, Yamini; Liu, Mingyi; Jung, Hyunjun; Zuo, Lei
Abstract: This paper presents a circuit to tune the electrical damping for optimal power harvesting at time varying excitation frequencies. Optimization of parameters, such as electrical damping to match the mechanical damping and the resonant frequency to match the excitation frequency have long been known. However, the electrical damping optimized at the resonant frequency is not necessarily the optimum point when the excitation frequency changes. This result is especially important in vibration energy harvesting systems since the vibration source is generally not at a single fixed frequency. The proposed circuit detects the excitation frequency and tunes the electrical damping based on a function, obtained from mechanical system modeling and simulation. A frequency detection circuit and a boost converter operating in critical conduction mode are used. Both modeling and experiment results show that the impedance tuning circuit provides the required optimal damping at different excitation frequencies and achieves a much broader bandwidth compared with the conventional system. When the excitation frequency increases to 1.1–1.4 times the natural frequency, the proposed adaptive damping tuning increases the power output by 30%–100% compared to the traditional one.